APLIKASI FORMULASI RANSUM DENGAN MENGGUNAKAN HIJAUAN LEGUMINOSA SEBAGAI PAKAN DASAR PENYUSUNAN RANSUM SAPI DI DESA JUNGUTAN KABUPATEN KARANGASEM - A. A. A. S, Trisnadewi; Cakra, I G. L. O.; Mudita, I M.; Wirawan, I W.; Puspani, E.; Budiasa, I K. M. (Buletin Udayana Mengabdi, 2013)
The community service was conducted in Jungutan Village, Karangasem Regency and was aimed to improve the farmers knowlegde especially the members of farmers groups about the utilization of leguminose forage as basal ration for ruminant. The services was conducted on Sunday, 2nd September 2012 at Wana Sari Groups of Farmers at Banjar Untalan, Jungutan Village, and attended by 20 from 24 total members of farmers’ groups (83.33%). The methods used were direct instruction and discussion to the farmers. Almost 43% members of farmers’ groups have been given leguminose besides grass and 57% only given grass as Bali cattle feed. The result of the services showed that the farmer’s awareness and knowlegde improved to give leguminose forage such as Gliricidia sepium, Caliandra callothyrsus, and Leucaena leucochepala, besides grass feeding as basal ration for Bali cattle. The utilization of forage need to be applied because of high energy and protein content in leguminose forage, therefore the dry matter consumption will improve. The nutrient requirement could fulfill and will impact to the improvement of Bali cattle growth and production.